Toward accurate CO2 and CH4 observations from GOSAT - Butz, André (Geophysical research letters, 2011)
The column-average dry air mole fractions of atmospheric carbon dioxide and methane and are inferred from observations of backscattered sunlight conducted by the Greenhouse gases Observing SATellite (GOSAT). Comparing the first year of GOSAT retrievals over land with colocated ground-based observations of the Total Carbon Column Observing Network (TCCON), we find an average difference (bias) of −0.05% and −0.30% for and with a station-to-station variability (standard deviation of the bias) of 0.37% and 0.26% among the 6 considered TCCON sites. The root-mean square deviation of the bias-corrected satellite retrievals from colocated TCCON observations amounts to 2.8 ppm for and 0.015 ppm for Without any data averaging, the GOSAT records reproduce general source/sink patterns such as the seasonal cycle of suggesting the use of the satellite retrievals for constraining surface fluxes.